2022
DOI: 10.58258/jisip.v6i3.3306
|View full text |Cite
|
Sign up to set email alerts
|

Komunikasi Antar Budaya Pasangan Kawin Campur di Indonesia

Abstract: As the world opens up and multicultural interactions increases, the same applies to intercultural relationships. In Indonesia, especially in the capital of Jakarta, people from different backgrounds of culture even countries are often met and some, fall in love. The study aims to understand and discover how individuals married to someone who is from different culture live, and the process of intercultural communication happen in an intimate relationship of a marriage. The study uses qualitative methodology wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The immediate solution is that they form a strong bond of commitment and the need to understand the existence of diversity. Furthermore, another study revealed that intercultural marriages have as many conflicts as monocultural marriages but require extra patience due to differences in addressing conflicts and require more time to adapt so that cultures assimilate each other (Budyanto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The immediate solution is that they form a strong bond of commitment and the need to understand the existence of diversity. Furthermore, another study revealed that intercultural marriages have as many conflicts as monocultural marriages but require extra patience due to differences in addressing conflicts and require more time to adapt so that cultures assimilate each other (Budyanto et al, 2022).…”
Section: Introductionmentioning
confidence: 99%